Comprehensive Assessment of Risk Factors for Childhood Obesity in Tashkent City, Uzbekistan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Obesity is one of the most significant public health problems in the twenty-first century. Taking a comprehensive approach to addressing this issue will allow us to consider all its aspects - dietary habits, physical activity, as well as socio-economic and socio-political factors in this field [1,2]. When considering them in terms of the epidemic spread of obesity as a problem that transcends temporal and national boundaries, particularly the alarming increase in obesity rates among children, it can be argued that this issue poses a threat to the health and well-being of future generations [7,8]. An important feature of the last decade is the increase in the number and change in the ratio of risk factors affecting children's health. Effective identification of these risk factors will help in targeted prevention of obesity development. Risk factors are determining health factors that have a negative impact on it.